Performan Puyuh Jantan (Coturnix coturnix japonica) Fase Pertumbuhan yang Diberi Tepung Buah Mengkudu (Morinda citrifolia l.) Sebagai Feed Additif - Geri Gunandi; Dini Widianingrum; Oki Imanudin (Tropical Livestock Science Journal, 2023)
This study aims to analyze the effect of feeding additive noni fruit flour (Morinda citrifolia L.) and measure what level of noni fruit flour (Morinda citrifolia L.) is the best for male quail (Coturnix coturnix japonica) performance in the growth phase. The research will be carried out using experimental methods which are arranged based on a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments consisted of P0 = 100% commercial feed + 0% noni fruit flour, P1 = 100% commercial feed + 1.5% noni fruit flour, P2 = 100% commercial feed + 3% noni fruit flour, P3 100% commercial feed + 4, 5% noni fruit flour and P4 = 100% commercial feed + 6% noni fruit flour. The results showed that giving noni fruit flour as a feed additive to the performance of male quail growth phase was not significantly different (P> 0.05) on body weight gain and was significantly different (P <0.05) on ration consumption, ration conversion, ration efficiency. and feed cost per Gain. The results of the average ration consumption between 180 - 190.8, ration conversion between 1.72 - 1.92, ration efficiency between 260.2200 - 290.9725 and feed cost per gain between Rp 12.395 - Rp 13.839. The best treatment is P4 because it is the best treatment in ration consumption and ration conversion.